Anion Exchange Membrane
By introducing cross connection points into the chloride exchange membrane and uniformly distributing the exchange groups, the problem of poor chemical stability of the existing chloride exchange membrane in high acid and high alkali environments is solved, and the effects of high ion exchange capacity and low surface resistance are achieved.
Patent Information
- Application Number
- JP2024563409
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2022-11-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing chloride exchange membranes have poor chemical stability in high acid and high alkali environments, and due to the existence of a support layer, it is difficult to improve the ion exchange capacity to improve physical properties.
Polyols with cross-connections are used as the exchange membrane material, and the cross-connection points are introduced into the polyol to improve the mechanical strength and chemical stability of the membrane while uniformly distributing the chloride exchange group on the membrane surface and pores.
It realizes the low surface resistance, high ion exchange capacity and excellent chemical stability of the chloride exchange membrane, and is suitable for high acid and high alkali environments.
Smart Images

Figure 2025514225000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an anion exchange membrane. [Background technology]
[0002] An ion exchange membrane is a synthetic resin membrane that selects cations and anions and allows only one of the ions to pass through. Among them, an anion exchange membrane is a synthetic resin membrane that has a functional group that bears a positive charge and selectively allows anions to pass through. Such an anion exchange membrane can be applied to water treatment systems such as electrodialysis, bipolar membrane electrodialysis, rechargeable desalination, and electrodeionization, or to systems such as fuel cells, water electrolysis, reverse electrodialysis, and redox flow batteries. In a system to which an anion exchange membrane is applied, acidic raw water or alkaline raw water is applied to a process, and acid or alkali may be generated during the operation of the raw water process. Therefore, a perfluorinated anion exchange membrane can be used as the anion exchange membrane, but it is expensive, and a hydrocarbon-based anion exchange membrane is applied in an actual system. However, the hydrocarbon-based anion exchange membrane has limitations in the process and conditions of application due to problems with chemical resistance. In addition, since a certain portion of the support exists in the anion exchange membrane, there is a limit to increasing the ion exchange capacity to improve the membrane properties. Summary of the Invention [Problem to be solved by the invention]
[0003] One aspect is to provide an anion exchange membrane which has low surface resistance, high ion exchange capacity, and excellent chemical resistance in the presence of high concentrations of acid and alkali.
[0004] Another aspect is to provide a method for producing the anion exchange membrane. [Means for solving the problem]
[0005] According to one aspect, A porous polymer support; an anion exchange polymer, The anion exchange polymer is located on the surface of the porous polymer support and inside the pores, the anion exchange groups of the anion exchange polymer are uniformly distributed on the surface of the porous polymer support and inside the pores; The porous polymer support has a basis weight of 10 g / m 2 or 60g / m 2 and The anion exchange membrane is provided, wherein the anion exchange polymer is a crosslinked product of a composition including a crosslinkable monomer represented by the following formula 1: [ka] In chemical formula 1, X - is F - , Cl - , Br - or I - It is.
[0006] The porous polymeric support may also be a nonwoven structure or a membrane structure.
[0007] The membrane structure may have a structure in which pores are regularly arranged, or may have a three-dimensional network structure.
[0008] The porosity of the porous polymer support is also 30% to 80%.
[0009] The porous polymer support may include one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylene sulfide, polyether ether ketone, polyether sulfone, polysulfone, polystyrene, polyarylene ether sulfone, and polyether ketone.
[0010] The thickness of the porous polymer support is also 10 μm to 110 μm.
[0011] The anion exchange membrane also has an average thickness of 10 μm to 200 μm.
[0012] The anion exchange membrane has an ion exchange capacity of 1.5 meq / g or more.
[0013] The surface resistance of the anion exchange membrane is 10 Ω cm 2 It is also the following.
[0014] The anion exchange membrane can be used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, and water electrolysis systems. Effect of the Invention
[0015] The anion exchange membrane according to one embodiment is a membrane comprising an anion exchange polymer that is a crosslinked product of a composition containing a crosslinkable monomer represented by the above-mentioned Chemical Formula 1 at 10 g / m 2 or 60g / m 2 The anion exchange polymer is a membrane located on the surface of a porous polymer support having a basis weight and inside the pores, and the anion exchange groups of the anion exchange polymer are uniformly distributed on the surface of the porous polymer support and inside the pores.
[0016] The anion exchange membrane may have a high ion exchange capacity and low surface resistance by increasing the content of anion exchange polymer in the anion exchange membrane. In addition, the anion exchange membrane has excellent chemical resistance and may be used under conditions of high concentrations of acid and alkali. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a conceptual diagram of a typical anion exchange membrane. [Diagram 2] 1 is a schematic diagram of an anion exchange membrane according to an embodiment; [Diagram 3]1 is a scanning electron microscope (SEM) photograph showing the structure of a porous polymer support used in the anion exchange membrane prepared in Example 4. [Figure 4] 1 is a schematic flow chart of a method for manufacturing an anion exchange membrane according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The anion exchange membrane will be described in detail below with reference to the examples of the present invention and the drawings. It will be obvious to those skilled in the art that the examples are merely presented for the purpose of explaining the present invention in more detail, and the scope of the present invention is not limited by these examples.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the case of any conflict, the present specification, including definitions, will control. Although methods and materials similar or equivalent to those described herein may be used in the practice or testing of the present invention, suitable methods and materials are described herein. As used herein, the term "comprises" means that it does not exclude other components, but also includes other components, unless specifically stated to the contrary. As used herein, the term "combination thereof" means a mixture or combination with one or more of the described components. As used herein, the term "and / or" means that it includes any and all combinations of one or more of the associated described items. As used herein, the term "or" means "and / or". As used herein, the phrase "at least one" or "one or more" before an element may be used to complete the entire list of elements, and not to complete the individual elements described above. In this specification, when a component is referred to as being disposed "on" or "above" another component, the component may be disposed directly on the other component, or there may be an intervening component between the components. On the other hand, when a component is referred to as being disposed "directly on" or "directly above" another component, there is no intervening component. In this specification, "~-based resin", "~-based polymer", "~-based polymer" and / or "~-based copolymer" are broad concepts including "~-resin", "~-polymer", "~-polymer", "~-copolymer", and / or "derivatives of ~-resin, ~-polymer, ~-polymer or ~-copolymer". In this specification, the term "polymers or copolymers crosslinked to those resins" means "polymers or copolymers crosslinked to the aforementioned resins".
[0020] FIG. 1 is a conceptual diagram of a typical anion exchange membrane.
[0021] 1, an anion exchange membrane 10 has an anion exchange polymer main chain 2 having a cationic functional group 1 disposed on a support 5. When a counter anion 3 and a co-cation 4 permeate from the left side to the right side, the anion exchange membrane 10 selectively allows the counter anion 3 to permeate.
[0022] In general, the anion exchange membrane 10 is required to have high permeability selectivity, low electrical resistance, excellent mechanical strength, high chemical stability, etc. Materials for the anion exchange membrane 10 include perfluorinated anion exchange membranes and hydrocarbon-based anion exchange membranes. Of these, the hydrocarbon-based anion exchange membranes are highly price competitive, but have poor chemical resistance and are limited in the processes and conditions in which they can be applied. In addition, the hydrocarbon-based anion exchange membranes have a certain support fraction, and there is a limit to increasing the ion exchange capacity to improve the membrane performance.
[0023] Taking note of such a point, the inventors of the present invention propose the following anion exchange membrane and a method for producing the same.
[0024] According to an embodiment, the anion exchange membrane includes a porous polymer support and an anion exchange polymer, the anion exchange polymer is located on the surface of the porous polymer support and inside the pores, the anion exchange groups of the anion exchange polymer are uniformly distributed on the surface of the porous polymer support and inside the pores, and the basis weight of the porous polymer support is 10 g / m. 2 or 60g / m 2 and the anion exchange polymer is also a cross-linked product of a composition comprising a cross-linking monomer represented by Formula 1: [ka] In chemical formula 1, X - is F - , Cl - , Br - or I - It is.
[0025] The anion exchange membrane according to an embodiment may have a high ion exchange capacity and low surface resistance by increasing the content of anion exchange polymer in the anion exchange membrane. In addition, the anion exchange membrane has excellent chemical resistance and may be used under conditions of high concentrations of acid and alkali.
[0026] FIG. 2 is a schematic diagram of an anion exchange membrane according to an embodiment.
[0027] 2, in the anion exchange membrane 40 according to one embodiment, an anion exchange polymer 31 having a cation functional group is located on the surface of a porous polymer support 20 and inside the pores 21. The anion exchange polymer 31 having a cation functional group is uniformly distributed on the surface of the porous polymer support 20 and inside the pores 21, so that a homogeneous anion exchange membrane 40 can be obtained. Such an anion exchange membrane 40 structure may have low surface resistance and high ionic conductivity. In addition, the porous polymer support 20 may have improved mechanical durability and high dimensional stability.
[0028] The anion exchange polymer is also a crosslinked product of a composition containing the crosslinkable monomer represented by Chemical Formula 1. The crosslinkable monomer represented by Chemical Formula 1 is a monomer in which two vinylbenzyl chlorides are crosslinked to a bi-functional cyclic diamine containing pendant chains to which a quaternary ammonium cation group is attached. The crosslinkable monomer represented by Chemical Formula 1 forms a rigid cage structure, and can improve ion exchange capacity while maintaining chemical stability even under high concentration acid or alkali conditions. Therefore, an anion exchange membrane containing such an anion exchange polymer can have excellent membrane performance. The "crosslinked product" refers to a cured product of a composition containing the crosslinkable monomer represented by Chemical Formula 1, as well as an initial reaction product, an intermediate reaction product, and a final reaction product.
[0029] The porous polymeric support may also be a nonwoven structure or a membrane structure.
[0030] The membrane structure may have a structure in which pores are regularly arranged or a three-dimensional network structure. The structure of such a membrane structure may be seen in FIG. 3, which will be described later. For example, the membrane structure may be prepared by mixing a polymer material with a low molecular weight wax, extruding the mixture into a film at high temperature, and then extracting the wax using a solvent to form a microporous structure, or may be prepared by a uniaxial or biaxial stretching process and a heat treatment process without using wax to form a pore structure. However, the membrane structure may be prepared by any manufacturing method available in the art, without being limited thereto.
[0031] The basis weight of the porous polymer support is 10 g / m 2 or 60g / m 2 The basis weight of the porous polymer support is 10 g / m 2 If the basis weight of the porous polymer support is less than 60 g / m, the physical durability and mechanical strength of the anion exchange membrane to be obtained by applying the porous polymer support cannot be improved. 2 If it exceeds this amount, the proportion of the porous polymer support in the anion exchange membrane will be too high, increasing the surface resistance of the anion exchange membrane and reducing the ion exchange capacity.
[0032] The porosity of the porous polymer support is 30% to 80%. For example, the porosity of the porous polymer support is 35% to 70%, 40% to 65%, 45% to 60%, or 45% to 55%. If the pore size and / or porosity of the porous polymer support is less than 30%, it is difficult to improve the physical durability and mechanical strength of the anion exchange membrane to be obtained as the porous polymer support. If the pore size and / or porosity of the porous polymer support is more than 80%, the proportion of the porous polymer support in the anion exchange membrane becomes too large, which may increase the surface resistance and reduce the ion exchange capacity.
[0033] The porous polymer support may include one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylene sulfide, polyether ether ketone, polyether sulfone, polysulfone, polystyrene, polyarylene ether sulfone, and polyether ketone. For example, the porous polymer support may be polyvinyl alcohol, polyethylene, or polypropylene. For example, the porous polymer support may be polyvinyl alcohol or polypropylene.
[0034] The thickness of the porous polymer support may be 10 μm to 110 μm. For example, the thickness of the porous polymer support may be 20 μm to 110 μm, 40 μm to 110 μm, or 60 μm to 110 μm. Within the thickness range of the porous polymer support, the surface resistance may be reduced and the ion exchange capacity may be increased.
[0035] The average thickness of the anion exchange membrane is 10 μm to 200 μm. For example, the average thickness of the anion exchange membrane is 12 μm to 150 μm. If the average thickness of the anion exchange membrane is less than 10 μm, the physical durability and handling of the anion exchange membrane are reduced, and there is a risk of membrane damage during operation when the module is assembled or after the system is applied, and the system operation performance may be reduced due to permeation of unnecessary ions. If the average thickness of the anion exchange membrane is more than 200 μm, the surface resistance is increased, and when applied to a system, the power consumption required for operation is increased, and the system operation performance may be reduced.
[0036] The ion exchange capacity of the anion exchange membrane is 1.5 meq / g or more. For example, the ion exchange capacity of the anion exchange membrane is 1.6 meq / g or more, 1.7 meq / g or more, 1.8 meq / g or more, 1.9 meq / g or more, 2.0 meq / g or more, 2.1 meq / g or more, 2.2 meq / g or more, 2.3 meq / g or more, or 2.4 meq / g or more.
[0037] The surface resistance of the anion exchange membrane is 10 Ω cm 2 For example, the surface resistance of the anion exchange membrane is 9.9 Ω cm 2 Below, 9.8Ω cm 2 Below, 9.7Ω cm 2 Below, 9.6Ω cm 2 Below, 9.0Ω cm 2 Below, 8.5Ω cm 2 Below, 8.0Ω cm 2 Below, 7.8Ω cm 2 Below, 7.6Ω cm 2 Below, 7.2Ω cm 2 Below, 6.5Ω cm 2 Below, 6.0Ω cm 2 Less than or equal to 5.0Ω cm 2 Below, 4.0Ω cm 2 Less than or equal to 3.0 Ω cm 2 It is also the following.
[0038] The anion exchange membrane can be used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, and water electrolysis. The anion exchange membrane can have excellent concentration and desalination performance.
[0039] A method for producing an anion exchange membrane according to another embodiment includes the steps of: providing a porous polymer support; preparing a composition for forming an anion exchange polymer, the composition including a crosslinkable monomer represented by the following Chemical Formula 1, a photoinitiator, and a solvent; impregnating the porous polymer support with the composition for forming an anion exchange polymer, thereby filling the surface and the inside of the pores of the porous polymer support with the composition; pressing a polyester film onto at least one surface of the porous polymer support filled with the composition to produce a laminate in which the polyester film and the porous polymer support are laminated; irradiating the laminate with light to crosslink the composition to form an anion exchange polymer, which is a crosslinked product of the composition, on the surface and the inside of the pores of the porous polymer support; and peeling off the polyester film from the porous polymer support having the anion exchange polymer formed on the surface and the inside of the pores to produce an anion exchange membrane, the porous polymer support being a nonwoven fabric structure or a membrane structure having a basis weight of 10 g / m. 2 or 60g / m 2 Also: [ka] In chemical formula 1, X - is F - , Cl - , Br - or I - It is.
[0040] The method for producing an anion exchange membrane can provide an anion exchange membrane that has low surface resistance, a large ion exchange capacity, and excellent chemical resistance in the presence of high concentrations of acid and alkali. FIG. 4 is a schematic flow chart of a method for manufacturing an anion exchange membrane according to an embodiment.
[0041] Referring to FIG. 4, first, a porous polymer support is provided (step S1).
[0042] The porosity of the porous polymer support is 30% to 80%. For example, the porosity of the porous polymer support is 35% to 70%, 40% to 65%, 45% to 60%, or 45% to 55%. If the pore size and / or porosity of the porous polymer support is less than 30%, it is difficult to improve the physical durability and mechanical strength of the anion exchange membrane to be obtained as the porous polymer support. If the pore size and / or porosity of the porous polymer support is more than 80%, the proportion of the porous polymer support in the anion exchange membrane becomes too large, which may increase the surface resistance and reduce the ion exchange capacity.
[0043] The porous polymeric support may also be a nonwoven structure or a membrane structure.
[0044] The porous polymer support may include one or more polymers selected from polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylene sulfide, polyether ether ketone, polyether sulfone, polysulfone, polystyrene, polyarylene ether sulfone, and polyether ketone. For example, the membrane structure may be polyvinyl alcohol, polyethylene, or polypropylene. For example, the membrane structure may be polyvinyl alcohol or polypropylene.
[0045] The thickness of the porous polymer support may be 10 μm to 110 μm. For example, the thickness of the porous polymer support may be 20 μm to 110 μm, 40 μm to 110 μm, or 60 μm to 110 μm. Within the thickness range of the porous polymer support, the surface resistance may be reduced and the ion exchange capacity may be increased.
[0046] The basis weight of the porous polymer support is 10 g / m 2 or 60g / m 2 The basis weight of the porous polymer support is 10 g / m 2If the basis weight of the porous polymer support is less than 60 g / m, the physical durability and mechanical strength of the anion exchange membrane to be obtained by applying the porous polymer support cannot be improved. 2 If it exceeds this amount, the proportion of the porous polymer support in the anion exchange membrane will be too high, increasing the surface resistance of the anion exchange membrane and reducing the ion exchange capacity.
[0047] Although the porous polymer support has hydrophobic properties, it cannot ensure sufficient wettability with the anion exchange polymer, and therefore cannot achieve the desired membrane performance.
[0048] To complement this, the method further includes a step of immersing the porous polymer support in a surfactant solution and drying it to prepare a porous polymer support having a hydrophilized surface before impregnating the porous polymer support with the composition for forming an anion exchange polymer. The surfactant may be any surfactant that can be hydrophilized in the art, and may be one or more materials selected from dodecylbenzenesulfonic acid (DBSA), alkylbenzenesulfonic acid (ABS), linear alkylbenzenesulfonic acid (LAS), alphasulfonic acid (AS), alphaolefinsulfonic acid (AOS), alcohol polyoxyethylene ether (AE), and alcohol polyoxyethylene ether sulfonic acid (AES). For example, the surfactant may be dodecylbenzenesulfonic acid. If the surfactant is bound to the surface of the porous polymer support, which is hydrophobic, through minority-minority interactions, the hydrophilic portion of the surfactant replaces the surface of the porous polymer support, and the surface of the porous polymer support can be hydrophilized. In this case, the surfactant can hydrophilize not only the outer surface of the porous polymer support, but also the entire surface of the internal pores. However, if the degree of hydrophilization of the porous polymer support is sufficient, or if the pores of the porous polymer support are large enough to be filled with the composition for forming an anion exchange polymer, this can be omitted.
[0049] The surfactant solution may contain 0.001 wt % to 6 wt % of a surfactant and a remaining amount of a solvent. For example, the surfactant solution may contain 0.01 wt % to 4 wt % of a surfactant and a remaining amount of a solvent, or 0.05 wt % to 3 wt % of a surfactant and a remaining amount of a solvent. If the surfactant is contained in the surfactant solution at less than 0.001 wt %, the surface of the porous polymer support is not hydrophilized and the composition for forming an anion exchange polymer is not filled into the pores of the porous polymer support. If the surfactant is contained in the surfactant solution at more than 6 wt %, the surfactant may be dissolved or the amount of the composition for forming an anion exchange polymer may be reduced.
[0050] The immersion may be performed for 0.1 to 10 minutes, for example, 0.5 to 5 minutes. If the immersion time is less than 0.1 minutes, the surface of the porous polymer support is not sufficiently hydrophilized, and the anion exchange polymer forming composition is not filled into the pores of the porous polymer support. If the immersion time exceeds 10 minutes, the production speed may be reduced and the production cost may be increased. The drying may be performed at a temperature of 40°C to 90°C for 1 to 20 minutes. For example, the drying may be performed at a temperature of 40°C to 80°C for 1 to 10 minutes.
[0051] Next, a composition for forming an anion exchange polymer is prepared, comprising a crosslinkable monomer represented by Formula 1, a photoinitiator and a solvent (Step S2).
[0052] The crosslinkable monomer represented by Chemical Formula 1 is a monomer in which two vinylbenzyl chlorides are crosslinked to a bifunctional cyclic diamine having pendant chains to which a quaternary ammonium cation group is attached. The crosslinkable monomer represented by Chemical Formula 1 forms a rigid cage structure, and has chemical stability even under high-concentration acid or alkali conditions, while improving ion exchange capacity. Therefore, an anion exchange membrane containing such an anion exchange polymer may have excellent concentration and desalination performance. The "crosslinked product" refers to a cured product of a composition containing the crosslinkable monomer represented by Chemical Formula 1, as well as an initial reaction product, an intermediate reaction product, and a final reaction product. The content of the crosslinkable monomer represented by Chemical Formula 1 is 30% to 70% by weight based on 100% by weight of the total composition for forming the anion exchange polymer.
[0053] The photoinitiator may be 0.01 to 2% by weight, or 0.1 to 1% by weight, based on 100% by weight of the entire composition for forming an anion exchange polymer. The photoinitiator may be any photoinitiator available in the art, and may be, for example, 2-hydroxy-2-methylpropiophenone. The solvent may be any solvent available in the art, and may be, for example, a water-soluble solvent such as water, methanol, or ethanol, or distilled water. The solvent may be included in the composition for forming an anion exchange polymer in the amount remaining after excluding the crosslinking monomer represented by Chemical Formula 1 and the photoinitiator.
[0054] Next, the porous polymer support is impregnated with the anion exchange polymer forming composition, and the surface and pores of the porous polymer support are filled with the composition (step S3). The impregnation may be performed for 0.1 to 10 minutes, for example, for 0.5 to 5 minutes. If the impregnation is performed for less than 0.1 minutes, the anion exchange polymer forming composition may not be sufficiently filled inside the pores of the porous polymer support, and the performance of the anion exchange membrane may be reduced or leakage may occur. If the impregnation is performed for more than 10 minutes, the production rate may be reduced and the production cost may be increased. Through the impregnation, the anion exchange polymer forming composition may be filled and filled into the pores of the porous polymer support, and the anion exchange polymer forming composition may cover the outer surface of the porous polymer support.
[0055] Next, a polyester film is pressed onto at least one surface of the porous polymer support filled with the composition to prepare a laminate in which the polyester film and the porous polymer support are laminated (Step S4).
[0056] The polyester film may be pressed onto the upper and / or lower surfaces of the porous polymer support by roll calendaring. The polyester film may be, for example, a polyethylene terephthalate film. The thickness of the polyester film may be 10 μm to 150 μm, for example, 20 μm to 120 μm, or 30 μm to 100 μm. If the thickness of the polyester film is less than 10 μm, a lamination failure such as wrinkles in the film may occur when laminating the porous polymer support filled with an anion exchange polymer. If the thickness of the polyester film is more than 150 μm, the thickness of the polyester film is too thick during the crosslinking reaction described below, and light is not sufficiently irradiated onto the porous polymer support, so that the crosslinking reaction does not occur sufficiently. The surface of the polyester film that contacts the porous polymer support may be untreated or may be treated for release. The use of such a film prevents the anion exchange polymer from being removed from the support surface by preventing the anion exchange polymer from bonding with the porous polymer support having a hydrophilized surface. The pressing may be performed at a temperature of 10° C. to 35° C., for example, at a temperature of 15° C. to 30° C., and at a pressure of about 0 bar to 5 bar. The pressure may be appropriately adjusted taking into consideration the thickness of the porous polymer support and the thickness of the polyester film.
[0057] Next, the laminate is irradiated with light to cause a crosslinking reaction of the composition, thereby forming an anion exchange polymer, which is a crosslinked product of the composition, on the surface of the porous polymer support and inside the pores (Step S5).
[0058] The light may be ultraviolet light, for example, UVA, UVB, UVC, or / and UVV. For example, the light irradiation uses UVC as ultraviolet light, and has an intensity of 2,000 mJ / cm. 2 or 10,000mJ / cm 2 For example, the light intensity is 2,000 mJ / cm 2 or 8,000 mJ / cm 2 This can be done with a light intensity of .
[0059] If the amount of ultraviolet light irradiated is less than the above range, the crosslinking reaction of the composition for forming an anion exchange polymer will not proceed smoothly, and if the amount of ultraviolet light irradiated is greater than the above range, the energy will be too strong and the porous polymer support and polyester film may melt or be carbonized.
[0060] Finally, the polyester film is peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores to prepare an anion exchange membrane (step S6). The peeling can be performed by pulling out the polyester film attached to the porous polymer support in the opposite direction using a release roll.
[0061] The present invention will be described in more detail below through examples. These examples are provided to more specifically explain the present invention, and the scope of the present invention is not limited to these examples. EXAMPLES
[0062] Example 1: Preparation of anion exchange membrane A 90 μm thick polyvinyl alcohol porous polymer support (basis weight: 22.5 g / m 2 , porosity: 80%) was prepared.
[0063] Separately, a solution of 4-vinylbenzyl chloride dissolved in methanol was added to a solution of 1,4-diazabicyclo[2,2,2]octane dissolved in methanol such that the molar ratio of vinylbenzyl chloride to 1,4-diazabicyclo[2,2,2]octane was 2:1, and the mixture was stirred at room temperature in an inert atmosphere to prepare a mixture. The mixture was filtered, washed with methanol, and then dried under vacuum at room temperature to obtain a crosslinkable monomer represented by the following formula 1.
[0064] 66% by weight of the crosslinkable monomer represented by Formula 1, 0.6% by weight of 2-hydroxy-2-methylpropiophenone (manufactured by Ciba) photoinitiator, and the remaining amount of distilled water were mixed to prepare a composition for forming an anion exchange polymer having a total weight of 100%.
[0065] The polyvinyl alcohol porous polymer support was impregnated with the composition for forming an anion exchange polymer, and the surface and the inside of the pores of the porous polymer support were filled with the composition. The porous polymer support filled with the composition was placed in a pressure roll, and a polyester film having a thickness of 50 μm was pressure-bonded to the upper and lower surfaces of the porous polymer support at room temperature, to produce a laminate in which the polyester film and the porous polymer support were laminated. The laminate was irradiated with 3,000 mJ / cm using UVC as ultraviolet light. 2 The porous polymer support was irradiated with a light of a certain amount to form an anion exchange polymer, which is a crosslinked product of the composition, on the surface of the porous polymer support and inside the pores. The polyester film was peeled off from the porous polymer support having the anion exchange polymer formed on the surface and inside the pores, to produce an anion exchange membrane. [ka] In formula 1, X - is Cl - It is.
[0066] Example 2: Preparation of anion exchange membrane A 125 μm thick polyvinyl alcohol porous polymer support (basis weight: 34.9 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cellulose acetate stearate having a porosity of 77% was used.
[0067] Example 3: Preparation of anion exchange membrane A 150 μm thick polyvinyl alcohol porous polymer support (basis weight: 46.4 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cellulose acetate stearate having a porosity of 74% was used.
[0068] Example 4: Preparation of anion exchange membrane A 60 μm thick polypropylene porous polymer support (basis weight: 25.0 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cation exchange membrane having a porosity of 55% was used.
[0069] Example 5: Preparation of anion exchange membrane A polypropylene porous polymer support with a thickness of 80 μm (basis weight: 40.7 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cation exchange membrane having a porosity of 45% was used.
[0070] Example 6: Preparation of anion exchange membrane A 110 μm thick polypropylene porous polymer support (basis weight: 52.8 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cation exchange membrane having a porosity of 48% was used.
[0071] Comparative Example 1: Production of anion exchange membrane A 210 μm thick polyvinyl alcohol porous polymer support (basis weight: 61.0 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cation exchange membrane having a porosity of 60% was used.
[0072] Comparative Example 2: Production of anion exchange membrane A 150 μm thick polypropylene porous polymer support (basis weight: 62.8 g / m 2 An anion exchange membrane was prepared in the same manner as in Example 1, except that a cellulose acetate stearate having a porosity of 29% was used.
[0073] Comparative Example 3: Production of anion exchange membrane A composition for forming an anion exchange polymer of 100% by weight was prepared by mixing 42% by weight of (3-acrylamidopropyl)trimethylammonium chloride (TCI), 14% by weight of N,N'-methylenebisacrylamide (Merck), 0.6% by weight of 2-hydroxy-2-methylpropiophenone (Ciba) photoinitiator, and the remaining amount of distilled water. An anion exchange membrane was prepared in the same manner as in Example 1, except that the above composition was used.
[0074] Analysis example 1: Scanning electron microscope (SEM) photograph The structure of the porous polymer support used in the anion exchange membrane prepared in Example 4 was observed using a scanning electron microscope (SEM) at a magnification of x30K. The scanning electron microscope used was S-5500 (Hitachi). The results are shown in Figure 3.
[0075] Referring to FIG. 3, it can be seen that the porous polymer support used in the anion exchange membrane prepared in Example 4 has a three-dimensional network structure.
[0076] Evaluation example 1: Physical property evaluation The physical properties of each of the anion exchange membranes produced in Examples 1 to 6 and Comparative Examples 1 to 3 were evaluated as follows.
[0077] (1) Surface resistance (Ω cm 2 ) Each anion exchange membrane was cut into a size of 5 cm x 5 cm to prepare a sample. The sample was immersed in a 0.5M NaCl aqueous solution for 24 hours. The sample was placed between electrodes for measuring sheet resistance, and the linear resistance (R 1 ), and the resistance of 0.5M NaCl solution (R 2 The measured resistance (R 1 ,R 2 ) into the following formula 1 to obtain the surface resistance (R m The results are shown in Table 1 below. [Formula 1] R m(Ω cm 2 )=(R 1 -R 2 )xS In formula 1, R m is the surface resistance of the anion exchange membrane, R 1 is the linear resistance of the anion exchange membrane, R 2 is the resistance of a 0.5M NaCl solution, S is the area of the electrode.
[0078] (2) Ion exchange capacity (IEC: ion exchange capacity (meq / g)) Each anion exchange membrane was cut to a size of 5cm x 5cm to prepare a sample. The sample was washed with distilled water and then excess water was removed with tissue paper. After filling a vial with 70ml of 1M NaCl solution, the sample from which the water had been removed was placed in the 1M NaCl solution and immersed for 12 hours or more to carry out a primary pretreatment. After that, the sample that had undergone the primary pretreatment was washed several times with distilled water and excess water was removed with tissue paper. 0.5M Na 2 CO 3 After filling a vial with 70 ml of the solution, the dehydrated sample was added to 0.5 M Na 2 CO 3 The sample was then placed in the solution and soaked for 12 hours or more for secondary pretreatment. After secondary pretreatment, the sample was removed from the vial and the remaining solution was diluted with 0.01M AgNO 3 Titration with the solution, and the AgNO 3 The volume of the solution was recorded. The sample was washed several times with distilled water and then dried in a hot air oven at 80°C for 15 minutes. After drying was completed, the weight of the dried anion exchange membrane was measured. The measured weight of the dried anion exchange membrane was substituted into the following Equation 2 to calculate the ion exchange capacity (IEC). The results are shown in Table 1 below. [Formula 2] IEC (meq / g) = (volume of titration reagent (ml) x 0.01) / weight of dried anion exchange membrane (g)
[0079] (3) Chemical resistance The anion exchange membranes manufactured in Example 2 and Comparative Example 3 were cut into 5 cm x 5 cm samples. The samples were dissolved in 1M NaOH solution and H 2 SO 4 After immersion in each of the 0.5M aqueous solutions, the surface resistance of each was measured according to the immersion time (days) as described above in "(1) Surface resistance (Ω cm 2 The results are shown in Tables 2 and 3. [Table 1]
[0080] Referring to Table 1, the porous polymer support of the anion exchange membrane prepared in Examples 1 to 6 has a basis weight of 22.5 g / m 2 or 52.8 g / m 2 The polyvinyl alcohol structure or polypropylene structure has a porosity of 45% to 80% and a thickness of 60 μm to 125 μm. The porous polymer supports of the anion exchange membranes manufactured in Comparative Examples 1 and 2 have basis weights or porosities outside the ranges of the examples of the present invention. In the composition for forming the anion exchange polymer of the anion exchange membrane manufactured in Comparative Example 3, a crosslinking monomer different from the crosslinking monomer represented by Chemical Formula 1 was used.
[0081] The anion exchange membranes produced in Examples 1 to 6 have a sheet resistance of 9.6 Ω cm compared to the anion exchange membranes produced in Comparative Examples 1 to 3. 2 and the ion exchange capacity (IEC) was improved to more than 1.6 meq / g.
[0082] [Table 2] [Table 3]
[0083] Table 2 shows the anion exchange membrane produced in Example 2, and Table 3 shows the anion exchange membrane produced in Comparative Example 3, when dissolved in 1M NaOH aqueous solution and H2 S O 4 The anion exchange membrane prepared in Example 2 was immersed in 0.5M aqueous solution and the sheet resistance was measured according to the immersion time. 2 SO 4 The anion exchange membrane prepared in Comparative Example 3 was immersed in a 1M NaOH aqueous solution and a 0.5M aqueous solution, and the sheet resistance change after 40 days was about 7% and about 4%, respectively. 2 SO 4 The anion exchange membrane produced in Example 2 was immersed in a 1M NaOH aqueous solution and a 0.5M H2O aqueous solution, and the sheet resistance change after 40 days was about 40% and about 11%, respectively. 2 SO 4 It was confirmed that the change in surface resistance after 40 days was small, demonstrating excellent chemical resistance.
[0084] As a result, it can be seen that the anion exchange membranes prepared in Examples 1 to 6 are suitable for use in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization, or water electrolysis systems.
Claims
1. A porous polymer support; an anion exchange polymer, The anion exchange polymer is located on the surface of the porous polymer support and inside the pores, the anion exchange groups of the anion exchange polymer are uniformly distributed on the surface of the porous polymer support and inside the pores; The porous polymer support has a basis weight of 10 g / m 2 60 g / m 2 and The anion exchange polymer is a crosslinked product of a composition including a crosslinkable monomer represented by the following formula 1: 【Chemistry 1】 In Chemical Formula 1, X - , F - , Cl - , B - Or I - It is.
2. The anion exchange membrane according to claim 1 , wherein the porous polymer support is a nonwoven structure or a membrane structure.
3. The anion exchange membrane according to claim 2 , wherein the membrane structure has a structure in which pores are regularly arranged or a three-dimensional network structure.
4. The anion exchange membrane according to claim 1 , wherein the porosity of the porous polymer support is 30% to 80%.
5. 2. The anion exchange membrane according to claim 1, wherein the porous polymer support comprises one or more polymers selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polyvinyl alcohol, polybenzimidazole, polyarylene sulfide, polyether ether ketone, polyether sulfone, polysulfone, polystyrene, polyarylene ether sulfone, and polyether ketone.
6. 2. The anion exchange membrane according to claim 1, wherein the porous polymer support has a thickness of 10 μm to 110 μm.
7. 2. The anion exchange membrane according to claim 1, wherein the average thickness of the anion exchange membrane is from 10 μm to 200 μm.
8. The anion exchange membrane according to claim 1 , wherein the anion exchange capacity of the anion exchange membrane is 1.5 meq / g or more.
9. The surface resistance of the anion exchange membrane is 10 Ω cm 2 2. The anion exchange membrane of claim 1, wherein:
10. 2. The anion exchange membrane according to claim 1, wherein the anion exchange membrane is used in electrodialysis, bipolar membrane electrodialysis, electrodeionization, capacitive deionization or water electrolysis systems.
Citation Information
Patent Citations
Ion exchange membrane
JP2013503038A
Ion exchange film, method of manufacturing the same, and electrodialysis reversal power generator
JP2014124562A
Polymeric functional film and method for producing the same
JP2015182047A
Composition for forming polymeric membrane, process for producing same, polymeric membrane, separation membrane module, and ion exchange device
WO2016027595A1